Estudo do nível de disclosure dos ativos intangíveis das empresas britânicas pertencentes ao índice FTSE 100 - Rolim, Márcio Viana (2009)
The recent trend towards consolidation of the global convergence of accounting standards, guided by international standards issued by the IASB (International Accounting Standards Board), expressed interest in identifying the level of disclosure of intangible assets in accordance with IAS 38, which is done by UK companies belonging to the FTSE 100 Index, from the Stock Exchange of London in 2006. Measuring the level of disclosure has been made possible with the content analysis of financial reports, drawing on an instrument of data collection guided from the studies of Botosani (1997), Eng and Mak (2003), Lansana (2004) and Goldner (2006). The results show that only 18.6% of the sample reached 100% for the disclosure of intangible assets, even legally obliged to do it. Tests were made to split the results by Pearson's correlation, path analysis, Canonical Correlation and Analysis of Variance by the bootstrap estimate, in order to explain the impact of the level of disclosure achieved by companies in relation to property information and financial performance rates reports provided by the Company Profile. The test results showed that only the variable ROA (Return on Assets), among all considered in this study, proved to be significant when related to the level of disclosure of companies. It is therefore concluded that the disclosure practices of financial reporting, companies belonging to the British FTSE 100 index in 2006, provided to external users need better preparation to meet the requirements of the IASB regarding the fulfillment of the Standard IAS 38 intangible assets. And even if, for example, information such as sector performance of the companies and external audit firm in charge, did not help to explain the level of disclosure achieved by the sample.